Study on wax deposition of heavy crude oil in pipelines - Nadia Eliza Natrah, Jamaluddin (2014)
This thesis presents wax deposition of heavy crude oil in pipelines study. Pipelines are widely used to transport crude oil. Wax deposition in a pipeline was caused by the high viscosity of the heavy crude oil, particularly if it is left untreated, may have severe consequences on the operational efficiency of a pipeline system. In order to overcome the wax deposition of the heavy crude oil, the crude oil is suggested to mix with water and emulsifier at certain conditions so that it will formed oil in water (0/W) emulsion. In this study, both chemical and physical properties of 07W emulsion that prepared by using three types of emulsifiers Coca Amide DEA (non-ionic and biodegradable surfactant that synthesis from coconut oil plus diethanolamine), Sodium Dodecyl Sulfate (anionic and biodegradable surfactant that synthesis from coconut oil only) with one type of conventional chemical emulsifier (Span 80) were examined. 01W emulsions with two different ratios (50-50% and 70-30%) were prepared at 1500 rpm mixing speed with the concentrations (0.3 wt%, 0.5 wt%, 1.0 wt% and 1.5 wt %) for each emulsifier to test the stability conditions. Instead of stability; shear rate, shear stress and viscosity were determined by Brookfield Viscometer. On the other hand, the droplet size was carried out by using Digital Carl Zeiss Microscope. Result shows that Sodium Dodecyl Sulfate at 1.5 wt% mixed with 70-30% 0/W obtained the most stable emulsion for transportation compared to the other two. Then, properties of heavy crude oil were tested via Fourier Transform Infrared (FTIR). The-properties are important to know in order to predict the occurrence of wax deposition during transportation. Next, the determination of Wax Appearance Temperature (WAT) using Koehler Cloud and Pour Point Bath. As the temperature decreases, crystalline structure will start to appear. Cloud and pour point of o/w emulsion using Sodium Dodecyl Sulfate which act as emulsifier are -1°C and -19°C respectively. Demulsification is the process of separation of water from the heavy crude oil. Crude oil need to be separate quickly from the water. This is to ensure the crude oil value can be maximized and the operating cost can be minimized. Demulsifiers (Hexylamine and Dioctylamine) with different concentrations (0.2 wt% and 0.5 wt%,1.0 wt% and 1.5 wt%) were used for transportation. The relative rates of water separation were characterized via beaker test. Hexylamine promotes the best coalescene of droplets compared with the other demulsifier that used in this study which is Dioctylamine.